Design and analysis of grid array antenna for total solution of highly-integrated 60-GHz radios - Tang, Wei. (2009)
In this paper, the current development of highly-integrated 60-GHz radios grid array antennas for reliable 60-GHz radio links will be examined. We design and analyze the grid array antennas with special attention to the differential feeding and the patterned ground plane. And two grid array antennas are integrated into one package. It propose the way of assembling it to the system printed circuit board, and result in a total solution of low cost as well as thin profile to highly-integrated 60-GHz radios. The antenna package is build in low temperature co-fired ceramic technology (LTCC) with feature size of only 13×13×1.265 mm3. It carries a 60-GHz radio die with flip-chip bonding, and achieves good antenna performance over the frequency range between 57GHz and 64 GHz. Hence, the design of the grid array antenna for 60-GHz radios is considered as the solution of radiating element. ii